2019
DOI: 10.1038/s41598-019-40234-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial comparing the effectiveness of structured-play (ENGAGE) and behavior management (TRIPLE P) in reducing problem behaviors in preschoolers

Abstract: Children’s behavior problems are a growing concern in our society; and are associated with a wide array of adverse lifespan outcomes. Current treatments are not without limitations and while effective for many, do not help all children. As such, additional treatment options are required. Sixty families of children aged 3 and 4 years participated. In order to participate, children needed to have a T-score of 60 or above on the parent rated Hyperactivity subscale on the BASC-2. Families were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Although studies generally found positive results, Poole concluded that most studies did not measure changes in the risk factors targeted in the campaign: only one program, Triple-P, had rigorous, controlled evaluations to indicate the positive impact at the individual and population levels. [131][132][133][134] The challenge to the practice community when only one program is evidence-based is the lack of options or implementation strategies for diverse populations and varying levels of funding.…”
Section: Primary Prevention Of Childhood Adversity and Traumamentioning
confidence: 99%
“…Although studies generally found positive results, Poole concluded that most studies did not measure changes in the risk factors targeted in the campaign: only one program, Triple-P, had rigorous, controlled evaluations to indicate the positive impact at the individual and population levels. [131][132][133][134] The challenge to the practice community when only one program is evidence-based is the lack of options or implementation strategies for diverse populations and varying levels of funding.…”
Section: Primary Prevention Of Childhood Adversity and Traumamentioning
confidence: 99%
“…There were no signi cant differences in treatment effects for ENGAGE and Triple P indicating that while they address self-regulation skill development very differently, both result in similar improvements in selfregulation. The study also found that there were no signi cant improvements in self-regulation during an 8-week waitlist period, suggesting improvements were the result of the interventions 17 .…”
Section: Introductionmentioning
confidence: 85%
“…En el caso de GAIM, no se han encontrado mejoras significativas en el funcionamiento ejecutivo de los participantes en el programa (Tamm et al, 2019). En el programa ENGAGE, se han llevado a cabo estudios que muestran mejoras significativas en la sintomatología TDAH (Healey & Halperin, 2015), si bien en un estudio controlado aleatorizado no mostró una eficacia superior a una intervención de entrenamiento a padres (Healey & Healey, 2019). Si bien la terapia de juego parece ser efectiva en la mejora de los síntomas de TDAH y de las funciones ejecutivas en preescolares (Rosas et al, 2019) se requiere mayor investigación para identificar los procesos que subyacen al TDAH y por tanto generar intervenciones más específicas que tengan un impacto directo en el trastorno.…”
Section: Intervención Cognitivaunclassified